2015
DOI: 10.1590/2359-3997000000091
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone resistance in two patients with papillary thyroid microcarcinoma and their BRAFV600E mutation status

Abstract: Resistance to thyroid hormone (RTH) is a rare autosomal dominant hereditary disorder. Here in, we report two patients with RTH in whom differentiated thyroid cancer was diagnosed. Two patients were admitted to our clinic and their laboratory results were elevated thyroid hormone levels with unsuppressed TSH. We considered this situation thyroid hormone resistance in the light of laboratory and clinical datas. Thyroid nodule was palpated on physical examination. Thyroid ultrasonography showed multiple nodules i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…An identical BRAF V600E mutation has been identified in solid cell nests in the thyroid and adjacent PTC ( 44 ), indicating that HT and PTC may be initiated by similar stem cell remnants, and may be etiologically related ( 7 ). In studied cases of RTH with PTC, BRAF V600E mutation testing was carried out in two studies ( 17 , 19 ) in the histological section and only one positive mutation was found ( 17 ). To the best of our knowledge, the present case report is the second patient to exhibit BRAF V600E mutation in PTC with RTH.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An identical BRAF V600E mutation has been identified in solid cell nests in the thyroid and adjacent PTC ( 44 ), indicating that HT and PTC may be initiated by similar stem cell remnants, and may be etiologically related ( 7 ). In studied cases of RTH with PTC, BRAF V600E mutation testing was carried out in two studies ( 17 , 19 ) in the histological section and only one positive mutation was found ( 17 ). To the best of our knowledge, the present case report is the second patient to exhibit BRAF V600E mutation in PTC with RTH.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study based on 637 medical records, Medenica et al ( 48 ) revealed that patients with increased serum TSH concentrations and/or AITD, exhibited an increased risk of thyroid malignancy. Since RTH is characterized by increased TH concentrations, accompanied by unsuppressed or increased serum TSH levels, whether patients with RTH are at increased risk of thyroid malignancy remains unknown ( 19 ). Owing to the low incidence of RTH and the lack of specific symptoms associated with the disorder, RTH is commonly misdiagnosed as hyperthyroidism or Grave's disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Karakose et al [32] reported two cases of RTH-β combined with papillary thyroid carcinoma that were stable after surgical treatment and replacement therapy. In both cases, the required does of L-T4 was very high, and suppression of TSH to within the goal range was difficult to achieve.…”
Section: Rth-β Accompanied By Papillary Thyroid Carcinomamentioning
confidence: 99%